Influence of Current or Former Smoking on Asthma Management and Control. Issue 5 (2008) - Boulet, Louis-Philippe; FitzGerald, J Mark; McIvor, R Andrew; Zimmerman, Sabrina; Chapman, Kenneth R
Abstract : BACKGROUND: In patients with asthma, smoking has been associated with accelerated decline in pulmonary function, poor disease control and reduced responsiveness to corticosteroids. OBJECTIVE: To assess the influence of current and former smoking on self-reported asthma control and health care use in a large population of asthma patients. METHODS: The present analysis was conducted following a telephone survey of adult Canadians aged 18 to 54 years who had physician-diagnosed asthma and a smoking history of less than 20 pack-years. RESULTS: Of 893 patients, 268 were former smokers and 108 were current smokers. Daytime and nighttime symptoms, absenteeism from work or school, emergency care use for asthma in the past year, and use of a short-acting bronchodilator without controller medication were reported more frequently by current smokers than non-smokers and former smokers. Former smokers were not significantly different from nonsmokers with respect to most asthma outcomes. CONCLUSIONS: Current smokers with asthma show evidence of poorer asthma control and greater acute care needs than lifelong nonsmokers or former smokers. These observations stress the importance of smoking cessation to help achieve asthma control.